PENGARUH BRAND IMAGE TERHADAP MINAT MENABUNG MAHASISWA DI BANK SYARIAH - Salma Saripatul Munawaroh; Ihrom Jaelani; Misbahul Khoer (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2024)
This research is motivated by field data indicating that in Indonesia, the majority of the population tends to save in conventional banks rather than in Islamic banks. This suggests a relatively low interest in saving among Indonesians in Islamic banks. The study aims to investigate the influence of brand image on students' interest in saving at Islamic banks. The research methodology employed is quantitative with a survey method. The population consists of 260 respondents, and the sample includes 158 students from STAI Putra Galuh Ciamis. Sampling was conducted using random sampling techniques based on the Slovin formula. Data were collected using a questionnaire comprising 22 items. Data analysis involved simple linear regression using SPSS version 25 software. Students' perceptions of the brand image of Islamic banks were positive, with an average score of 3.935, indicating a high rating. Students' interest in saving at Islamic banks stemmed from perceived benefits, needs, and the variety of Sharia-compliant products offered. The brand image variable showed a t-value of 10.996, which is greater than the critical t-value of 1.975, with a significance level of 0.000 < 0.05. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, indicating that the brand image variable (X) significantly influences students' interest in saving (Y). The research findings indicate that brand image accounts for 43.7% of the variance in students' interest in saving at Islamic banks.